1983
DOI: 10.1073/pnas.80.20.6239
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond flash photolysis study of carbon monoxide binding to the beta chain of hemoglobin Zürich [beta 63(E7)His leads to Arg].

Abstract: Binding of carbon monoxide to .8 chains of hemoglobin Zurich has been studied by flash photolysis over the time range of nanoseconds to seconds at temperatures from 20 to 300 K. From 20 to 200 K a single rebinding process (process I) is seen, characterized by a distribution of barrier heights with a peak enthalpy of 2.3 kj/mol. Above 200 K some ligands escape from the pocket into the matrix, and above 260 K recombination from the solvent sets in. Process I is visible up to 300 K, but above 200 K its rate remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…The rebinding barrier height for SW H64G below 160 K was found to be smaller than for native SW MbCO, which is in agreement with our results for human Mb H64A. Recently, a study of Leu-29 mutants in human Mb showed an increase in a low-frequency IR peak, and the bimolecular CO rebinding of these mutants was found to be (40,41), consistent with the trends we are seeing.…”
Section: Resultssupporting
confidence: 81%
“…The rebinding barrier height for SW H64G below 160 K was found to be smaller than for native SW MbCO, which is in agreement with our results for human Mb H64A. Recently, a study of Leu-29 mutants in human Mb showed an increase in a low-frequency IR peak, and the bimolecular CO rebinding of these mutants was found to be (40,41), consistent with the trends we are seeing.…”
Section: Resultssupporting
confidence: 81%
“…3a) is a phenomenon that is familiar to us from studies of heme proteins in this temperature range (1,2,25,26). In heme proteins, the nonexponential behavior has been explained with the concept of CS: At low temperatures, the proteins are frozen into many slightly different structures, the CS, with different activation enthalpies, HBA, for ligand binding.…”
Section: Methodsmentioning
confidence: 99%
“…In heme proteins, the nonexponential behavior has been explained with the concept of CS: At low temperatures, the proteins are frozen into many slightly different structures, the CS, with different activation enthalpies, HBA, for ligand binding. The inhomogeneous ensemble of protein molecules is characterized by a distribution of enthalpy barriers, g(HBA).t If we assume that kAB << kBA, the fraction of proteins that have not yet rebound a ligand at time t after photodissociation is described by N(t, T) = f g(HBA)e-kBA(HBT)tdHBA [31 The temperature dependence of the rate coefficient kBA(HBA, T) is usually given by the transition-state expression (26) kBA(HBA, T) = ABA(T/To)eHBAIRT.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of the distal His (E7) residue on the functional properties of Mb and Hb has been studied for natural and recombinant mutants. For example, the natural Hb Zurich ([Argp63] Hb) exhibits a substantial increase in the rate of CO recombination after photodissociation (Dlott et al, 1983;Scott et al, 1985). This increase has been attributed to the effect of the large guanidinium group of arginine, which exchanges hydrogen bonds with the propionate side chains of the heme and contributes to enlarge the entrance of the heme pocket (Tucker et al, 1978).…”
mentioning
confidence: 99%